1979
DOI: 10.1073/pnas.76.5.2326
|View full text |Cite
|
Sign up to set email alerts
|

Induction of prostaglandin E synthesis in normal and neoplastic macrophages: role for colony-stimulating factor(s) distinct from effects on myeloid progenitor cell proliferation.

Abstract: The biosynthesis of prostaglandin E (PGE) by normal and neoplastic macrophages is intrinsically linked to their synthesis of, and exposure to, myeloid colony-stimulating factors (CS-factors). The defect in responsiveness to endotoxin lipopolysaccharide (LPS) by macrophages from C3H/Hej mice extends equally to the synthesis of CS-factor and PGE. However, C3H/Hej macrophages can be stimulated to synthesize PGE by treatment with agents other than LPS [zymosan, tuberculin purified protein derivative, concanavalin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

1979
1979
1995
1995

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(42 citation statements)
references
References 28 publications
0
41
0
1
Order By: Relevance
“…As further evidence of the complexity of prostaglandin effect, the addition of PGF2G, to the mononuclear cell cultures gave a different response. Whereas low concentrations of PGF2G showed dose-dependent stimulation of colony formation, at the higher concentrations tested PGF2c, (10 ,M) was inhibitory. This inhibition may have been a result of PGE2 contamination or a PGE2-like effect seen at high doses of PGF2<,.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…As further evidence of the complexity of prostaglandin effect, the addition of PGF2G, to the mononuclear cell cultures gave a different response. Whereas low concentrations of PGF2G showed dose-dependent stimulation of colony formation, at the higher concentrations tested PGF2c, (10 ,M) was inhibitory. This inhibition may have been a result of PGE2 contamination or a PGE2-like effect seen at high doses of PGF2<,.…”
Section: Discussionmentioning
confidence: 82%
“…As part of a probable physiological control to prevent runaway myelopoiesis, monocyte/ macrophage PGE2 synthesis is initiated (3,9). When highly purified colony-stimulating factor was tested it could be shown to directly cause PGE2 synthesis (10). Thus myelopoiesis appears to be regulated by two diffusable, monocyte/macrophage-derived agents with the specificity residing in the positive limb of the dual feedback loop.…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic analysis indicates that constitutive prostaglandin E production by mouse macrophages (26) and human monocytes is not detected during the first 3 h in culture. These results negate the contribution of endogenously produced prostaglandin E in this system.…”
Section: Discussionmentioning
confidence: 95%
“…The ultimate degree of CFU-GM expansion to mature granulocytes and macrophages is dependent upon GM-CSF levels (32,33). At high prostaglandin concentrations, particularly as a consequence of GM-CSF induced monocyte-macrophage prostaglandin production (20,26,28,34), clonal CFU-GM expansion is limited (8)(9)(10)28) …”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude the possibility that a subpopulation of lymphoid, granulocytic or tumour cells which also adhere might play an accessory role in this growth-stimulatory process. It is possible that tumour cells produce colony-stimulating activity (CSA) (Okabe et al, 1978) which has been shown to be capable of influencing prostaglandin E production (Kurland et al, 1979) and, furthermore, contaminating polymorphonuclear leucocytes can affect CSA by release of lactoferrin (Broxmeyer et al, 1978). However, it has previously been reported that phagocytic depletion alone (which would not remove lymphoid cells) markedly reduces tumour-colony growth (Hamburger et al, 1978) reinforcing the central regulatory role of the macrophage.…”
Section: Methodsmentioning
confidence: 99%